Predictors of Suicide Ideation and Attempt Planning in a Large Sample of New Zealand Help-Seekers - Shepherd, Daniel; Taylor, Stephen; Csako, Rita; Liao, An-Tse; Duncan, Renee (Frontiers in Psychiatry, 2022)
Aim: Suicide is a major public health concern worldwide. The present study explores the risk factors for suicide ideation and suicide attempt planning by analyzing anonymized data collected by a New Zealand telephone helpline. Method: A nation-wide helpline, Lifeline Aoteroa, provided data from distressed callers. The analyzed sample consisted of 32,889 counseling calls of clients with a wide range of presenting issues. Frequency analysis and multivariable logistic regression were adopted to determine risk and protective factors associated with two types of suicide behaviors: suicide ideation and suicide planning. Results: Risk factors for suicide ideation and suicide planning included: hopelessness, sadness, fear, not coping with symptoms of mental health issues, mild/moderate severity self-harm, severe self-harm, urge to self-harm, alcohol and/or drug addiction, suicide in family, sexual domestic abuse. Unexpectedly, feeling anxious was determined to be a protective factor. Conclusion: Risk factors were identified for both suicide ideation and for suicide attempt planning. While some of these risk factors have been reported in existing literature, there are also risk factors unique to the present study that could inform and improve suicide-screening procedures administered by clinicians or helplines.